2016
DOI: 10.1021/acs.molpharmaceut.5b00903
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of the Amorphous Ezetimibe Drug by Confining Its Dimension

Abstract: The purpose of this paper is to investigate the influence of nanoconfinement on the molecular mobility, as well as on the physical stability, of amorphous ezetimibe drug. Two guest/host systems, ezetimibe-Aeroperl 300 and ezetimibe-Neusilin US2, were prepared and studied using various experimental techniques, such as X-ray diffraction (XRD), differential scanning calorimetry (DSC), and broadband dielectric spectroscopy (BDS). Our investigation has shown that the molecular mobility of the examined anticholester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 46 publications
(65 reference statements)
1
52
0
Order By: Relevance
“…The adsorbents; Aeroperl ® 300 (A300) and Neusilin ® US2 (NUS) were obtained from Evonik industries (Germany) and Fuji Chemical Industry (Japan), respectively. More detailed information, about the chemical nature and particle properties of the adsorbents, are described in Table 5 [54,55,60]. [54] 300 300 Particle Size (µm) [60] 30-40 60-120 Pore Volume (ml/g) * [54] 2.2 4 Peak Pore Size (nm) ** [54] ≈25 ≈800 Predominant Type of Pores [54,55] Mesoporous (2-50nm) Macroporous (>50nm) * based on the mercury intrusion-extrusion technique.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…The adsorbents; Aeroperl ® 300 (A300) and Neusilin ® US2 (NUS) were obtained from Evonik industries (Germany) and Fuji Chemical Industry (Japan), respectively. More detailed information, about the chemical nature and particle properties of the adsorbents, are described in Table 5 [54,55,60]. [54] 300 300 Particle Size (µm) [60] 30-40 60-120 Pore Volume (ml/g) * [54] 2.2 4 Peak Pore Size (nm) ** [54] ≈25 ≈800 Predominant Type of Pores [54,55] Mesoporous (2-50nm) Macroporous (>50nm) * based on the mercury intrusion-extrusion technique.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…Usually, the improvement of an amorphous drug's physical stability by MS is explained by one of two mechanisms: (i) confinement of the API molecules inside the MS pores or (ii) molecular interactions between functional groups of the API molecules and the surface of the stabilizing excipient [28,33,34]. It is worth noting that, in the case of the former mechanism, it is possible to reach even an eternal stabilization effect [35]. Such a situation might occur only when the pore diameter of the employed MS is smaller than the critical crystal nuclei of the API, as well as if all API molecules are incorporated inside the pores.…”
Section: Introductionmentioning
confidence: 99%
“…A general understanding of the T g behavior on confinement is lacking. 60 Neat CNC did not demonstrate any porosity according to the nitrogen adsorption experiments. The lack of porosity in neat CNC indicates that the CNC nanoparticles are in close contact in the spray-dried material which prevents the nitrogen from penetrating into the material.…”
Section: Intraparticle Confinementmentioning
confidence: 84%
“…Knapik et al 60 reported that the T g of ezetimibe loaded into the mesoporous Aeroperl 300 was increased with 0.8 C and increased with 6.7 C when loaded into Neusilin US2 compared with neat amorphous ezetimibe. Furthermore, the T g of glycerol was increased as a function of the pore size when confined in MCM-41.…”
Section: Intraparticle Confinementmentioning
confidence: 99%